Restructuring and social safety nets in Russia and Ukraine - social security influence on labor mobility: Possible opportunities and challenges - Marek Góra; Oleksandr Rohozynsky (Center for Social and Economic Research (CASE), 2009)
The paper discusses the issue of labor force mobility in a broad sense, and analyses how changes in social security policy and the structure of the social safety net (SSN) affects different aspects of labor force mobility. The text is structured as follows: Introduction, then follows Chapter 2, which provides an overview of the labor market and social safety net developments in Russian and Ukraine over the last decade, as well as discusses common features of these countries. The Chapter 3 establishes theoretical models for different aspects of labor force mobility, discusses the availability of data on Russia and Ukraine to test these models, and provides a statistical analysis of the data. The Chapter 4 discusses results of the statistical analysis. The final chapter discusses policy conclusions that can be derived from comparison of the effect of the SSN on labor mobility in these two countries, and extends them to all countries in transition.
Keywords: H55; J32; J62; J68; P36; P52; 330; labor market; social safety net; social security; labor force; mobility; employment; Unemployment; transition countries; public policy; Russia; Ukraine; Soziale Sicherheit; Sozialpolitik; Arbeitsmobilität; Russland; Ukraine